Parliamentary System in Nigeria: An Appraisal of its Practice and Challenges - Abbass, Isah Mohammed (European Scientific Journal, ESJ, 2026)
Nigeria’s experience with the parliamentary system of government during the First Republic, 1960-1966, is appraised and evaluated based on the structural and contextual factors that shaped its practice and challenges. Drawn from its historical trajectories, parliamentary crises, and constitutional infirmity, the study critically examines how the Westminster model was engrafted, adopted and adapted within Nigeria’s multi-ethnic federal framework. The architectural designs and foundations of both the parliamentary and presidential systems were established to serve vested interests; hinged on democratic corruption by usurping the principles of due process and rule of law. These are usually followed by excessive and abusive use of executive power.The paper further argues that while the system fostered regional party development and legislative debate, it was undermined by regionalism, weak party discipline, ethno-political rivalry, and the absence of a national consensus imbued within the system. The January 1966 military coup exposed the system’s vulnerability to elite capture, manipulation and constitutional crises. The paper concludes that the collapse of the parliamentary system was not due to inherent flaws in the model alone but to its incompatibility with Nigeria’s political sociology at independence. It further reflects on contemporary calls for a return to parliamentarism, highlighting lessons on executive-legislative relations, accountability, and national integration that remain relevant to Nigeria’s ongoing constitutional quagmire.